Spiking neurons with spatiotemporal dynamics and gain modulation for monolithically integrated memristive neural networks - Qingxi Duan (Nature Portfolio, 2020)
Designing energy efficient and scalable artificial networks for neuromorphic computing remains a challenge. Here, the authors demonstrate online learning in a monolithically integrated 4 × 4 fully memristive neural network consisting of volatile NbOx memristor neurons and nonvolatile TaOx memristor synapses.